The Swedish Fiscal Policy Framework and Intermediate Fiscal Policy Targets - Torben M. Andersen (Swiss Journal of Economics and Statistics, 2013)
Sweden is a front-runner in defining intermediate targets for fiscal policy (fiscal rules) as well as in setting up an independent fiscal council to monitor and comment on developments. Swedish public finances are among the most sound in the OECD having been able to consolidate public finances and ensure fiscal sustainability, and they have maintained room for fiscal manoeuvre also during the financial crisis. This paper takes a closer look at the Swedish case as the stepping stone for a more general discussion of how to set intermediate targets for fiscal policy and the role fiscal councils may have in strengthening political accountability and thus ultimately credibility of fiscal policy. The Swedish fiscal framework is compared to the fiscal compact for EU countries, and it is argued that it has a number of desirable features.
Keywords: H6; 330; debt; debt brake; fiscal rules; Sweden